The Nielsen Project: North American Reception of Carl Nielsen’s Symphonies - Tetzlaff, Regitze Ida (Danish Yearbook of Musicology, 2017)
North American Nielsen reception including concerts and recordings has been crucial to the international reputation of Nielsen since the 1960s. Recently The Nielsen Project, a collaboration between the Danish record label Dacapo and the New York Philharmonic Orchestra, has performed and recorded all of Nielsen’s symphonies and the concertos in the new DXD format, released as a CD box set in 2015. As part of my research for my MA thesis I have visited New York and conducted interviews with the protagonists of this project and done research in American archives. The purpose was to conduct an investigation of how this new project related to American Nielsen reception of earlier decades in order to establish a notion of how views on Carl Nielsen as a composer and of his symphonies have been changing in American reception history.